Segmentation Analysis Of International Students At Islamic Religious Universities To Increase The Number Of International Students - Lubis, Fauzi Arif; Daulay, Aqwa Naser; Harahap, Rahmat Daim (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
This research aims to segment the formation of students from the Study Program at the Faculty of Islamic Economics and Business at Islamic Religious Colleges in order to increase the number of international students. To solve the problem of this research, the researcher used a qualitative approach. In this study, the researcher aims to analyze the segmentation of international students at Islamic Higher Education Institutions through segmentation testing by examining four components: demographics, geography, psychographics, and behavior. After obtaining test results based on indicators and segment developments, characteristics, structural segmentation, and similarities, the effectiveness of the market will be evident, and segmentation can be established. Based on the findings and discussions in this study, in the Geographic Segmentation, most of the distribution comes from Malaysia (90%), while the rest comes from Thailand (10%). In the Demographic Segmentation, the majority of respondents attended High School (65%) before entering the university, and the income of international students' parents can be categorized into 4,000 – 6,000 Malaysian Ringgit per month and 34,000 – 36,000 baht per month. In the Psychographic and Behavioral Segmentation, the basis for respondents choosing their target university is mostly due to having a feasibility cooperation with their home country (35%), indicating that the degree obtained can be valid in their home country and curriculum compatibility. Seventy-five percent believe that an English preparation program is necessary to facilitate communication and reading reference books during their studies. Furthermore, the way respondents obtain information and motivation to study at their current university is mostly through recommendations from seniors/alumni (60%). Their expectations of the campus are that the degree can be used for job requirements in their home country (45%).